Description of Meeting Blood Needs in Negative Rhesus Patients At dr. Zainoel Abidin Aceh - Rachmad Cahyadi; Zuriana Zuriana (Universitas STRADA Indonesia, 2020)
The fulfillment of blood needs in Rhesus negative patients based on the blood group that is fulfilled is blood type O as much as 42 blood bags (30.8%) and those that are not met blood group AB are 25 bags of blood (18.3%). Fulfillment of blood needs in Rhesus negative patients based on Rhesus that is fulfilled is Rhesus positive as much as 14,000 blood bags (100%) and those that are not met Rhesus negative are as many as 73 blood bags (53.6 5). Fulfillment of blood needs in Rhesus negative patients based on the inpatient room 26 bags of blood (19.1%) were fulfilled in the midwifery inpatient room and 42 bags of blood (30.8%) were not fulfilled.The study shows that the fulfillment of blood needs in Rhesus negative patients is smaller than what is fulfilled at UTD dr. Zainoel Abidin Aceh Hospital in September 2019-April 2020